Logistics Efficiencies and Processes (L.E.A.P.) - Zeron, Eva; Hall, Brice; Qualls, Tanner; Winslett, Marc (My University, 2015)
The warranty lab at NACCO Materials Handling Group (NMHG) is responsible for making the final decision on whether or not a part has a warrantable fault. Because of the increased part traffic flowing in and out of the warranty lab there have been issues with organization, work flow, and facility layout. Data collection has been completed for shipping and receiving processes of the lab, as well as the process flow of a warranted part. Two time studies have been completed on receiving and shipping parts to determine the amount of non-value added time. From the time study, it was determined that 22% of the time spent on a single part is considered non-value added time. Additionally, 27% of the total amount of time spent shipping and receiving parts per day is considered non-value added time. A final layout was designed in conjunction with NMHG’s feedback. A distance based cost analysis was conducted in order to compare to the original layout. A final workbench will be recommended based on NMHG’s feedback. The final recommendations for the floor layout and mobile workbench have a cost of $1,838. Over the five year time horizon and assuming a 3% interest, the net present value is $3,051. When the floor layout and mobile workbench are implemented NMHG can expect to see savings from less distance traveled, safety, and organization. Their initial investment will be paid back in 1.72 years with an internal rate of return of 51%.
Keywords: Warrantable fault; Shipping and receiving processes; Facility layout; 5S